Introducing .NET 4.5 - Mackey, Alex; Stewart Tulloch, William; Krishnan, Mahesh (Apress : Imprint: Apress, 2012)
Microsoft has introduced a large number of changes to the way that the .NET Framework operates. Familiar technologies have being altered, best practices replaced, and developer methodologies adjusted. Many developers find it hard to keep up with the pace of change across .NET's ever-widening array of technologies. The introduction of Windows 8 and its new style of applications only compounds the problem. You may know what's happening in C#, but what about the latest innovations in the cloud? How is that going to affect your work? What possibilities do the new async capabilities bring? What you need is a roadmap. A guide to help you see the innovations that matter and to give you a head start on the opportunities available in the new framework. Introducing .NET 4.5 is designed to provide you with just that roadmap. It serves as a no-nonsense primer that will help experienced .NET developers understand the impact of the new framework and the technologies that co-exist with it. This book will keep you updated on the changes and help you to seize new opportunities confidently and quickly.